Intracranial Otogenic Complications in Adults: New Factors Influencing its Onset - Sahibzada Fawad Khan, Sayyed Muddasir Shah, Haider Zaman, Mubashar Ullah Jan (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To identify new factors influencing the onset of intracranial otogenic complications in adults. Study Design: Retrospective cohort Place and Duration of Study: Department of ENT, Nowshera Medical College, Qazi Medical Complex Nowshera from 1st October 2019 to 31st October 2020. Methodology: One thousand and nine hundred cases within the age of 40-78 years were enrolled. The data before viral pandemic of corona virus was compared with the data gained during pandemic. The intracranial complications included meningitis, abscess of subdural/epidural or brain, sigmoid sinus and or internal jugular vein-thrombosis. The period since registration till surgery varied from 6-24 hours with an average 10-14 hours. The confirmation of coronavirus in every patient was done before admission by using reverse transcription polymerase-chain reaction through nasopharyngeal swab. Results: The mean age of 50.3±11.2 years. It was observed that there were cases of intracranial complication as 4 in pre covid time while ten were reported in the covid pandemic times. The Venous-sinus thrombosis was present in 60% of cases during covid pandemic while only in 25% before covid duration presenting a significant raise during pandemic time. Cardiovascular comorbidity was also presented significantly higher as 50% respectively in covid pandemic time with highest probability. Brain abscess and coagulopathies were also found significantly higher in covid pandemic times than in the duration before the covid, an Odd Ratio of 0.04(0.003; 1.05) 95% CI. Conclusion: The new factors for influencing onset of intracranial otogenic complications in adult venous sinus thrombosis, brain abscess, coagulopathies and comorbidities as cardiovascular diseases.